Cold-Water Immersion and Athletic Recovery: A Systematic Review of Randomized Controlled Trials (2000–2024) - Patel, Sachin; Shukla, Anshuman; Sharma, Renu; Chahal, Archana; Das, Rajdeep (Physical Education Theory and Methodology, 2025)
Background. Cold-water immersion (CWI) is a commonly used recovery strategy among athletes, but evidence of its effectiveness remains inconsistent due to variations in protocols and outcome measures. Objectives. This systematic review aimed to evaluate the effects of CWI on post-exercise recovery in athletes, focusing on physiological, performance, and perceptual outcomes. Materials and Methods. Following PRISMA guidelines and PROSPERO registration (CRD420251068097), four electronic databases (PubMed, Web of Science, Scopus, and ProQuest) were searched for randomized controlled trials (RCTs) published between 2000 and 2024. Studies were included if they achieved a PEDro score ≥6. Twelve RCTs met the inclusion criteria. Data were synthesized narratively, supported by vote-counting and harvest plots, as heterogeneity prevented meta-analysis. Results. CWI consistently reduced delayed-onset muscle soreness (DOMS) and muscle damage biomarkers (e.g., creatine kinase, lactate dehydrogenase) within 24–48 hours post-exercise. Several trials also reported improvements in subjective recovery. The effects on neuromuscular performance (e.g., sprinting, countermovement jump) were mixed and appeared context-dependent. Evidence regarding inflammatory markers (e.g., IL-6, CRP) was limited and inconclusive. Variability in water temperature, immersion duration, and timing contributed to inconsistent outcomes across studies. Conclusions. The findings indicate that moderate-to-strong evidence supports the short-term use of CWI to reduce muscle soreness and damage, as well as to enhance perceptual recovery. The effects on performance and inflammation remain unclear, emphasizing the need for protocol standardization. CWI remains a practical tool for athletes, especially in high-load or congested schedules, but its application should be individualized.